Plasma volume status predicting clinical outcomes in patients undergoing transcatheter edge‐to‐edge mitral valve repair - Ai Kagase; Masanori Yamamoto; Takahiro Tokuda; Ryotaku Kawahata; Hiroto Nishio; Tetsuro Shimura; Ryo Yamaguchi; Mitsuru Sago; Yuki Izumi; Mike Saji; Masahiko Asami; Yusuke Enta; et al. (ESC Heart Failure, 2025)
Abstract Aims Plasma volume status (PVS) is recognized as a marker of systemic congestion, but its clinical utility in patients with mitral regurgitation (MR) undergoing transcatheter edge‐to‐edge mitral valve repair (M‐TEER) has not been well established. This study aimed to evaluate the prognostic significance of PVS in these patients. Methods and results Data from 3763 patients who underwent M‐TEER were analysed from a Japanese multicentre registry. Patients were classified into functional MR (FMR) and degenerative MR (DMR) according to MR aetiology, and the median PVS values for each were calculated (FMR 12.7, DMR 14.4). The median value was used as the cut‐off, stratifying the cohort into a high PVS group (n = 1882) and a low PVS group (n = 1881). All‐cause mortality, cardiovascular death, and heart failure (HF) hospitalization between these two groups were compared up to 3 years in the overall, FMR, and DMR populations. The cumulative incidence rates of all‐cause mortality, cardiovascular death, and HF hospitalization were higher in the high PVS group than in the low PVS group (47.0% vs. 22.2%, P < 0.001, 31.6% vs. 13.6%, P < 0.001, and 35.9% vs. 24.7%, P < 0.001, respectively). Similar trends in terms of all‐cause mortality, cardiovascular death, and HF hospitalization were observed in the FMR and DMR cohorts (all P < 0.05). In the multivariate Cox regression analysis, the high PVS compared with the low PVS group was independently associated with the increased risk of all‐cause death (hazard ratio [HR], 1.02; 95% confidence interval [CI], 1.01–1.03; P < 0.001), cardiovascular death (HR, 1.02; 95% CI, 1.01–1.03, P < 0.001) and HF hospitalization (HR, 1.02; 95% CI, 1.01–1.02, P < 0.001). An independent association between a high PVS and all‐cause death, cardiovascular death, and HF hospitalization was also found in FMR and DMR sub‐groups (all P < 0.05) while reducing MR severity to moderate or less after M‐TEER was associated with improved outcomes in both the high and low PVS groups. Conclusions Preoperative PVS is a strong independent prognostic marker in patients undergoing M‐TEER, correlating with increased risk of mortality and HF hospitalization. PVS may provide valuable clinical insights for patient stratification and management strategies in M‐TEER patients.